2016
DOI: 10.1016/j.ajic.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk of infection following colonization with carbapenem-resistant Enterobactericeae: A systematic review

Abstract: Background-Carbapenem-resistant Enterobacteriaceae (CRE) have emerged as important health care-associated pathogens. Colonization precedes infection but the risk of developing infection amongst those colonized with CRE is not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
177
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(217 citation statements)
references
References 24 publications
12
177
1
5
Order By: Relevance
“…Colonisation with CRE is most often defined by gastrointestinal tract carriage identified through the use of a rectal swab or faecal sampling [31]. Gut microbiota carriage can be identified through clinical culture even when the patient remains asymptomatic.…”
Section: The Role Of Asymptomatic Carriage In Community-associatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonisation with CRE is most often defined by gastrointestinal tract carriage identified through the use of a rectal swab or faecal sampling [31]. Gut microbiota carriage can be identified through clinical culture even when the patient remains asymptomatic.…”
Section: The Role Of Asymptomatic Carriage In Community-associatedmentioning
confidence: 99%
“…Although colonisation is generally a prerequisite for infection, it is largely unknown what percentage of colonised patients will progress to active infection. A recent systematic review pooled 1806 hospital-based patients identified as colonised with CRE at the time of admission and found that 299 (16.5%) progressed to clinical infection [31]. Isolation of hospital patients with known CRE colonisation at the time of admission, whether symptomatic or not, has led to a significant reduction of nosocomial transmission of CRE infection [18].…”
Section: The Role Of Asymptomatic Carriage In Community-associatedmentioning
confidence: 99%
“…This data is relatively novel as the most studies of Enterobacteriaceae colonization have focused almost exclusively on gastrointestinal colonization with resistant Enterobacteriaceae. 7 Most Enterobacteriaceae skin colonization occurs in the groin and axilla, and it has been suggested before that the groin may act as a permanent source of Enterobacteriaceae skin colonization in some patients. 8 Both the groin and axilla are rich in sweat glands and this may explain why these sites are most frequently colonized, and why males, with more active sweat glands, are more commonly colonized.…”
Section: Discussionmentioning
confidence: 99%
“…Travel history is important for all patients with infections, as knowledge of local pathogens in recent travel destinations may be useful in directing empiric therapy. As an example, travelers to areas endemic for multidrug resistant (MDR) Enterobacteriaceae have an increased risk of acquisition of an MDR Enterobacteriaceae colonizer and patients who are colonized with carbapenem-resistant Enterobacteriaceae (CRE) have a 16.5 % risk of infection with CRE [11]. …”
Section: Epidemiology Of Ssti In the Usa Europe And Worldwidementioning
confidence: 99%